From hydroelectricity to the National Grid: Harewood House and the history of electrification in Britain, 1900–1940. Issue 1 (2nd January 2018) - Kay, Michael; Gooday, Graeme
ABSTRACT: This paper explores the changing experiences of electricity consumption in British country houses up to the early years of national electricity supply. We identify three stages of domestic electrification: the 'experimental' stage, when the technology was viable only for limited household purposes; the 'fashionable' stage when electrical lighting was rendered an aesthetic luxury; and finally the normalisation stage, when electricity was treated as a commodity, no longer a curiosity. We focus on this previously little-discussed final stage with evidence taken from a typical example: Harewood House, Leeds, at which electricity was installed in 1901. Like other pre-Grid country houses, Harewood had to be self-sufficient in electricity production for longer than households in urban areas where networked supply was available sooner. Since country houses could often employ hydroelectric generating systems, their electricity supply was both fully controlled by residents and free to use (discounting initial installation costs). However, in the 1930s, the arrival of the National Grid in rural areas brought not only new opportunities for centralised supply, but also new challenges. Our paper draws on new archival evidence from Harewood House to examine the adjustments required to electrical energy consumption when switching from self-generated electricity to a metered external supply.